Evidence of the role of marketing arrangements and valuation methods in improving beef quality - Liu, Yanyan; Muth, Mary K.; Koontz, Stephen R.; Lawrence, John D. (Wiley, 2009)
Low and inconsistent beef quality has been blamed by some for the losses of beef's share of total meat consumption. Tighter vertical coordination through use of alternative marketing arrangements and more precise price signaling through use of different cattle valuation methods may help improve beef quality because these mechanisms facilitate information exchange enabling producers to respond better to consumer demand. For the congressionally mandated Livestock and Meat Marketing Study, we modeled differences in levels and variances of cattle quality associated with particular marketing arrangements and valuation methods using fed cattle purchase data from 29 large U.S. beef packing plants for October 2002 through March 2005. Results indicate fed cattle procured through marketing agreements and packer ownership had higher and more consistent quality compared to other types of arrangements. Auction market cattle quality was the most inconsistent. Fed cattle valued using carcass weight with a grid were associated with higher and more consistent quality. [EconLit Citation: Q13]. © 2009 Wiley Periodicals, Inc.